2002
DOI: 10.1093/jnci/94.5.334
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in the Receipt of Cancer Treatment

Abstract: A disproportionate number of cancer deaths occur among racial/ethnic minorities, particularly African Americans, who have a 33% higher risk of dying of cancer than whites. Although differences in incidence and stage of disease at diagnosis may contribute to racial disparities in mortality, evidence of racial disparities in the receipt of treatment of other chronic diseases raises questions about the possible role of inequities in the receipt of cancer treatment. To evaluate racial/ethnic disparities in the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
601
9
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 836 publications
(638 citation statements)
references
References 140 publications
20
601
9
2
Order By: Relevance
“…34 Several studies have revealed disparities because of race/ethnicity, older age, and geographic location in breast cancer care, including the receipt of RT after BCS. 12,13,27,[35][36][37][38][39][40][41][42][43] The present study, however, is the first to document a disparity in the receipt of RT because of race/ethnicity and SES in a single region within the state of California, and an age disparity throughout the entire state. LA, the most populous of the California regions with the largest number and highest percentage of African American and Hispanic residents in this study, is the only region where the association of RT after BCS varied by race/ethnicity.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…34 Several studies have revealed disparities because of race/ethnicity, older age, and geographic location in breast cancer care, including the receipt of RT after BCS. 12,13,27,[35][36][37][38][39][40][41][42][43] The present study, however, is the first to document a disparity in the receipt of RT because of race/ethnicity and SES in a single region within the state of California, and an age disparity throughout the entire state. LA, the most populous of the California regions with the largest number and highest percentage of African American and Hispanic residents in this study, is the only region where the association of RT after BCS varied by race/ethnicity.…”
Section: Discussionmentioning
confidence: 91%
“…3,9,24 Our previous research revealed that women with triple-negative breast cancer were significantly more likely to be African American or Hispanic and live in socioeconomically deprived areas, 14,15 and age was found to have an important role in determining the ER/PR/HER2 subtype. 16,17 Although racial disparities in breast cancer treatment and outcomes have been previously well documented, 3,[25][26][27] the interplay between race/ethnicity and SES and their respective causative effect on breast cancer outcomes remain controversial. 28 Furthermore, it remains difficult to completely unravel the intertwining aspects of these factors in addition to tumor biology and age.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 These inequities are attributable to the social determinants of health; the environmental conditions in which people live that affect a wide array of health, functioning, and life outcomes. 3 These social determinants of health, such as safe and affordable housing, access to education and employment, and personal safety, culminate in a wide range of financial, structural, and personal obstacles to completing cancer care.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, experience with other cancers suggests that differences in healthcare use and access to surgical therapy may be involved, with minority racial and ethnic populations less likely to receive appropriate care. 10 Racial and ethnic inequities in the delivery of appropriate treatment for HCC, especially surgery, may explain the observed survival disparities. 7,8 Given these observations, we performed a broad, population-based analysis using 2 major national databases to investigate trends in the survival of patients with HCC over the past 4 decades.…”
mentioning
confidence: 99%